RANCANGAN APLIKASI SISTEM PAKAR KEPRIBADIAN MANUSIA BERBASIS ANDROID - Prawidya Destarianto; Arief Febriyanto (Jurnal Teknologi Informasi dan Terapan, 2019)
Human beings are creatures intact holistic or combination of elements of biological, psychological, social and spiritual. As biological beings, humans are composed of organ systems that are used to maintain life. As psychological beings, humans have personality structure, behavior as a manifestation of mental and thinking skills and intelligence. Personality is any pattern of behavior and human nature which is unique both hereditary emerged as a response and how adaptation to any kind of stimulation that comes from the environment or from within yourself. The uniqueness depending on the type of personality. We humans do not fully know what and how our personality characteristics. The problem that arises is that we as humans do not fully know what and how the characteristics of our personality. We as a unique individual, which means that human beings are different from one another and are not exactly the type of personality, that's why we need to know our personalities. The next problem that arises is the media to find out what and how our personalities are very difficult and rare to be found, unless we come to a psychologist to conduct a series of psychological tests to determine the process of our personality. Therefore, based on the above problems can be made an application to determine the type of personality that is an expert system-based human personality tests android.